An Analysis of the Impact of Digipay Utilization on the Expenditure Efficiency of Central Government Work Units - Muqimuddin, Saifan Abdulloh; Mahi, Benedictus Raksaka (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2025)
Research Originality — Existing empirical research shows that digital marketplace platforms can improve expenditure efficiency, yet evidence in the public sector, especially in developing countries, remains scarce. This study provides novel empirical evidence by examining the implementation of Digipay in central government work units to assess its impact on expenditure efficiency. Research Objectives — Digipay was designed as a digital payment platform to address several challenges in the government procurement process. This study therefore examined the impact of its adoption on procurement efficiency at the central government work unit level. Research Methods — This study used the 2022 fiscal year data primarily drawn from the Online Monitoring Sistem Perbendaharaan dan Anggaran Negara (OMSPAN) database and the Ministry of Finance’s Digipay database. The analysis applied the Mahalanobis Distance Matching (MDM) method with the Kernel Matching algorithm, supplemented by regression adjustment, to estimate the effect of Digipay. Empirical Results — The findings indicated that Digipay adoption has enhanced procurement efficiency among central government work units nationwide. Empirical estimates suggested that its use increased efficiency by 2.59%. Implications — Based on these results, the Ministry of Finance is encouraged to further optimize Digipay utilization to strengthen procurement efficiency across central government work units, which serve as the primary implementing unit of government expenditure.